Lived citizenship for persons in vulnerable life situations Theories and practices - Fjetland, Kirsten Jæger; Gjermestad, Anita; Lid, Inger Marie (Scandinavian University Press (Universitetsforlaget), 2022)
The need for care and welfare services puts elderly and persons with intellectual disabilities, chronic conditions and dementia in vulnerable situations. How are they recognized as citizens with rights and duties? In this book, the challenges and resources for persons in vulnerable life situations are made visible through a relational and rightsbased perspective of citizenship. The chapters are based on the authors' studies of lived citizenship in different contexts within professional health and welfare practices and the everyday life of citizens in vulnerable life situations in Norway. This edited book is the result of contributions from the interdisciplinary research group 'Citizenship', hosted at the Faculty of Health Studies at VID Specialized University. The aim of the research group is exploring and enhancing citizenship through theoretical as well as empirical studies. The book brings contributions to scholars and researchers in the broad field of interdisciplinary disability and citizenship studies, as well as graduate students.